Literary Journalism of Shanul Haq Haqqi - Irfan Shah (بازیافت, 2020)
Shanul Haq Haqqee (15th September, 1917 - 11th October, 2005) was a versatile genius having multi-dimensional vision and knowledge. He was at a time great linguist, lexicographer, researcher, scholar, critic, translator, biographer, fiction writer, an acknowledged great poet, a story writer for children, humorist, copywriter and a publicist. His respected father Moulvi Ahteshamuddin was also a great lexicographer, poet, researcher and writer of great eminence. Shanul Haq Haqqee's creative works is found in various forms of Urdu literature in which he has shown his creativity and exhibited his new experiences in them. In his works his approach and vision had various angles and innovations. His writings in respect of credibility and correctness of language attained status of a certificate of perfection. His special interest in lexicography represents his command on the subject and theme. During his honorary appointment in Urdu Development Board, Karachi, he served for many noble services which includes his lexicographic work on Urdu dictionary and issuance of quarterly "Urdu Nama". He also remained associated as Chief Editor Urdu Monthly "Mah-e-Nau" Karachi.